Intercultural Communication Skills among Prospective Turkish Teachers of German in the Context of the Comparative Country Knowledge Course - (:unkn) unknown (EDAM, 2012)
This study develops and provides a sample implementation of a seminar for the 'Comparative Country Knowledge' course taught in the German Language Teaching departments of Turkish universities. The study was conducted with the participation of forty-seven 1st year students attending a German Language Teaching department. As part of the study, Cultural Values Model consisting of four dimensions was used to develop intercultural communication skills. Students' views on learning attitudes and problems in the two cultures were examined on the basis of this model. At the end of the seminar, students were asked to fill out a questionnaire to evaluate the seminar*. The results of the study showed that prospective teachers acquired different cultural perspectives in the Comparative Country Knowledge course. The model seems to have made a significant contribution to students' intercultural communication skills.
Keywords: Interculturality; Intercultural Learning; Comparative Regional Studies; Intercultural Communication Competence; Teacher Education; German Language Teaching